Prophylactic Ibuprofen Does Not Improve Pain With IUD Insertion. Issue 4 (April 2015) - Bednarek, Paula H.; Creinin, Mitchell D.; Reeves, Matthew F.; Cwiak, Carrie; Espey, Eve; Jensen, Jeffrey T.
<x xml:space="preserve">Abstract</x> ABSTRACT Rates of unintended pregnancy are high in the United States due in large part to inadequate and inconsistent use of intrauterine devices (IUDs) and other long-acting reversible contraceptives. The safety and efficacy of IUD are well established, but concerns about difficulty with IUD insertion and procedure-related pain are a major barrier to their utilization, especially among nulliparous women. Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used to reduce pain prior to insertion of an IUD. However, no data have demonstrated significant pain relief with NSAIDs prior to insertion, including use specifically in nulliparous women. Providing ibuprofen or other NSAIDs without evidence of benefit exposes patients to their harmful effects. The largest trial investigating use of NSAIDs prior to IUD insertion used ibuprofen 400 mg, which is a dose lower than commonly recommended in the United States. The aim of this randomized, double-blind, placebo-controlled trial was to determine whether administration of ibuprofen 800 mg prior to IUD placement would reduce pain associated with the procedure among US nulliparous and multiparous women. All subjects were given a choice of either the copper T380A IUD or the LNG 52 mg IUS. The trial was conducted as a planned substudy of a multicenter trial evaluating IUD insertion approximately 2 to 6 weeks following first-trimester uterine aspiration for induced or spontaneous abortion. Subjects were enrolled between June 2007 and February 2009 at 4 US academic medical centers. Pain was measured after speculum insertion (baseline) and immediately following IUD insertion using a 100-mm visual analog scale. There were no significant differences between groups in sociodemographic characteristics or baseline visual analog scale scores. A total of 202 women were randomized to receive ibuprofen 800 mg (n = 101) or placebo (n = 101) 30 to 45 minutes prior to IUD insertion. The median pain score with IUD insertion was similar in the 2 groups: 41.5 mm in the placebo group and 38.0 mm in the ibuprofen group (P = 0.50). Mean and median pain scores did not differ between groups when nulliparous and parous women were evaluated separately. Nulliparous women reported about twice as much pain with IUD insertion compared with multiparous women (approximately 60 vs 30 mm). No differences were noted in median pain scores based on age, IUD type, history of dysmenorrhea, previous IUD use, or number of days since aspiration (P > 0.05 for all comparisons). These data show that administration of ibuprofen 800 mg prior to IUD insertion does not reduce procedure-related pain in US women and affirm that more pain with IUD insertion is reported in nulliparous than multiparous women.